THE INFLUENCE OF FINANCIAL MANAGEMENT BEHAVIOR, FINANCIAL LITERACY, AND RISK TOLERANCE ON INVESTMENT DECISIONS - Ni Putu Keisya Ulan Pramesti; I Dewa Nyoman Badera (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study aims to analyze the influence of financial management behavior, financial literacy, and risk tolerance on investment decisions among accounting students in Bali. The research sample consisted of 312 respondents from Udayana University, Ganesha University of Education, Mahasaraswati University Denpasar, Warmadewa University, and University of National Education. Data were collected through online questionnaires and analyzed using the Partial Least Squares Structural Equation Modeling (SEM-PLS) technique. The results indicate that financial management behavior, financial literacy, and risk tolerance have a positive and significant effect on students’ investment decisions.